Strategi Pemenuhan Neraca Pangan Padi dalam Mendukung Kebijakan Ketahanan Pangan di Desa Kiangroke, Banjaran. - Arya Sugihman; Tarlani (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. This study aims to analyze food security in Kiangroke village, Banjaran District. Data obtained through land suitability analysis, natural resource management, and agricultural policies are used to evaluate the challenges and potentials in achieving food security in this area. The research findings indicate that Kiangroke village faces challenges in meeting the increasing food needs of its population. Although rice production in this region has good potential, paddy loss needs to be addressed to achieve an optimal amount of rice. In addressing these challenges, comprehensive strategies are needed, such as improving agricultural productivity, developing agricultural infrastructure, and strengthening the capacity of farmers and agricultural institutions. The food security program in Kiangroke, Banjaran District can focus on identifying the potential of natural resources, developing organic farming, and enhancing access to local markets. Collaboration among the government, farmers, and other stakeholders is key to the successful implementation of this program. By implementing appropriate strategies, it is expected that Kiangroke village can achieve a higher level of food security and improve the well-being of farmers and the entire rural community. Abstrak. Penelitian ini bertujuan untuk menganalisis ketahanan pangan di desa kiangroke Kecamatan Banjaran. Data yang diperoleh melalui analisis kesesuaian lahan, pengelolaan sumber daya alam, dan kebijakan pertanian digunakan untuk mengevaluasi tantangan dan potensi dalam mencapai ketahanan pangan di wilayah ini. Hasil penelitian menunjukkan bahwa desa Kiangroke menghadapi tantangan dalam memenuhi kebutuhan pangan masyarakat yang semakin bertambah. Meskipun produksi beras di wilayah ini memiliki potensi yang baik, penyusutan gabah perlu diperhatikan untuk memperoleh jumlah beras yang optimal. Dalam menghadapi tantangan ini, diperlukan strategi yang komprehensif, seperti peningkatan produktivitas pertanian, pengembangan infrastruktur pertanian, dan penguatan kapasitas petani dan kelembagaan pertanian. Program ketahanan pangan di Kiangroke Kecamatan Banjaran dapat difokuskan pada identifikasi potensi sumber daya alam, pengembangan pertanian organik, dan peningkatan akses ke pasar lokal. Kolaborasi antara pemerintah, petani, dan pemangku kepentingan lainnya menjadi kunci keberhasilan implementasi program ini. Dengan menerapkan strategi yang tepat, diharapkan Desa Kiangroke dapat mencapai tingkat ketahanan pangan yang lebih baik dan meningkatkan kesejahteraan petani serta masyarakat desa secara keseluruhan.